Antiviral Role of IFITM Proteins in Classical Swine Fever Virus Infection - Li, Cheng (Viruses, 2019)
The proteins IFITM1, IFITM2, and IFITM3 are host effectors against a broad range of RNA viruses whose roles in classical swine fever virus (CSFV) infection had not yet been reported. We investigated the effect of these proteins on CSFV replication in mammalian cells. The proteins were overexpressed and silenced using lentiviruses. Confocal microscopy was used to determine the distribution of these proteins in the cells, and immunofluorescence colocalization analysis was used to evaluate the relationship between IFITMs and the CSFV endosomal pathway, including early endosomes, late endosomes, and lysosomes. IFITM1, IFITM2, or IFITM3 overexpression significantly inhibited CSFV replication, whereas protein knockdown enhanced CSFV replication. In porcine alveolar macrophages (PAMs), IFITM1 was mainly located at the cell surface, whereas IFITM2 and IFITM3 were mainly located in the cytoplasm. Following CSFV infection, the distribution of IFITM1 changed. IFITM1, IFITM2, and IFITM3 colocalization with Lamp1, IFITM2 with Rab5 and Rab7, and IFITM3 with Rab7 were observed in CSFV-infected cells. Collectively, these results provide insights into the possible mechanisms associated with the anti-CSFV action of the IFITM family.